ChemInform Abstract: Convenient and Mild Epoxidation of Alkenes Using Heterogeneous Cobalt Oxide Catalysts. Issue 39 (23rd September 2014) - Banerjee, Debasis; Jagadeesh, Rajenahally V.; Junge, Kathrin; Pohl, Marga‐Martina; Radnik, Joerg; Brueckner, Angelika; Beller, Matthias
Abstract A general epoxidation of aromatic and aliphatic olefins, including renewable olefins such as (R)‐(+)‐limonene (V), geraniol acetate (VII), and vitamin derivative (IX), are developed.